2019
DOI: 10.1186/s12888-019-2032-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical and mental multimorbidity in suicidal thoughts and behaviours in a Scottish population cohort study

Abstract: BackgroundPhysical illness and mental disorders play a significant role in fatal and non-fatal suicidal behaviour. However, there is no clear evidence for the effect of physical and mental illness co-occurrence (multimorbidity) in suicidal ideation and attempts. The aim of the current study was to investigate, whether physical/mental health multimorbidity predicted suicidal thoughts and behaviours as outcomes.MethodsData from the West of Scotland Twenty-07 cohort were analysed. Twenty-07 is a multiple cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
4
13
1
2
Order By: Relevance
“…The results of the present study showed that older adults with limited physical functioning had a higher rate of depressive symptoms and suicidal ideation. This result is consistent with previous studies which show that suicidal ideation and behaviors increase if someone has a particular physical condition [19,20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study showed that older adults with limited physical functioning had a higher rate of depressive symptoms and suicidal ideation. This result is consistent with previous studies which show that suicidal ideation and behaviors increase if someone has a particular physical condition [19,20].…”
Section: Discussionsupporting
confidence: 93%
“…Many studies suggest that the majority of those with physical illness have additional psychiatric disorders [2,[11][12][13][14]19]. A previous study found that the risk of suicide increases if someone has a mental illness along with a physical illness [19]. The results of the present study showed that older adults with limited physical functioning had a higher rate of depressive symptoms and suicidal ideation.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In China, multimorbidity is common among middle-aged and older adults, with a prevalence of nearly 50% [ 5 , 6 ]. Compared with single chronic conditions, multimorbidity has been associated with more outpatient visits, longer hospital stays, increased health care costs [ 7 , 8 ], more mental complaints or disorders [ 9 , 10 ], lower quality of life [ 11 ], and increased risk of mortality [ 12 , 13 ]. Accordingly, preventing the rising prevalence of multimorbidity has become an important clinical and public health challenge in China as well as other countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are based on small, nonrepresentative samples of the population, including a sample limited to armed forces veterans (Scott et al, 2010;Thompson et al, 2014). Studies exploring physical health conditions co-occurring with mental health conditions have similarly suggested an increased likelihood of suicidal thoughts and behaviours but not above the independent risk of mental ill-health alone (Kavalidou et al, 2017(Kavalidou et al, , 2019. However, this may not translate into an actual risk of suicide as the epidemiology of suicide ideators or attempters differs from that of suicide completers (O'Connor and Kirtley, 2018).…”
Section: Introductionmentioning
confidence: 99%